Copper(I)-promoted trifluoromethylation of indole derivates with concomitant C–C bond formation to access fused tricyclic indoles. Issue 13 (25th March 2015) - Zhu, Huiming; Liu, Huanlong; Feng, Xiaolong; Guo, Ruixia; Chen, Xueyan; Pan, Zhenhua; Zhang, Lantong
Graphical abstract: Abstract: Modern drug discovery has created an increasing demand for new methods of trifluoromethylation. Herein a novel method for the synthesis of trifluoromethylated fused tricyclic indoles by copper(I) iodide as catalyst has been successfully developed under mild conditions. The corresponding trifluoromethyl indoles were obtained with good to excellent yields (62–89%) and the reaction applies to a different range of functional groups.